From Family Based to Industrial Based Production: Local Economic Development Initiatives and the HELIX Model - Pennink, Bartjan W (The Asian Journal of Technology Management (AJTM), 2012)
To build a strong local economy, good practice tells us that each community should undertake a collaborative, strategically planned process to understand and then act upon its own strengths, weaknesses, opportunities and threats. From this perspective we start with the local communities but how is this related to the perspective from the Helix model in which three actors are explicitly introduced: the Government, the Industry and the Universities? The purpose of local economic development (LED) is to build up the economic capacity of a local area to improve its economic future and the quality of life for all. To support  the Local Economic Development in remote areas,   a program  has been developed based on the LED frame work of the world bank. This approach and  the experiences over  the past years with this program are  described in the first part.  In the second part of the paper, We analyse work done with that program with the help of the social capital concept and the triple helix model.  In all cases it is important to pay attention to who is taken the initiative after the first move (and it is not always the governance as actor) and for the triple helix we suggest  that the concepts of (national) Government, Industry and University need a translation to Local Governance Agency, Cooperation or other ways of cooperation of local communities and Local Universities. Although a push from outside might help  a local region in development the endogenous factors are  also needed. Keywords: Triple Helix model, Local Economic Development, Local Actors, Double Triangle within the Helix Model